2003
DOI: 10.1046/j.1351-0754.2003.0566.x
|View full text |Cite
|
Sign up to set email alerts
|

Climatic effects on soil trophic networks and the resulting humus profiles in holm oak (Quercus rotundifolia) forests in the High Atlas of Morocco as revealed by correspondence analysis

Abstract: Summary Multivariate methods have been widely used for revealing the structures of communities, and in this paper we explore one particular method, namely correspondence analysis (also called reciprocal averaging), for studying humus profiles by the ‘method of small volumes’. The present study was done on humus profiles under holm oak (Quercus rotundifolia), an evergreen Mediterranean species, in the High Atlas of Morocco. Three sites (1500 m, 1700 m, 1900 m altitude) and 2 years (1999 and 2002) were compared.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…In contrast to previous studies (Ponge 1993;Sadaka and Ponge 2003) and probably because of hierarchy, HMFA did not devote an axis to depth gradient. Nevertheless, careful examination of results shows that depth is a key criterion in distinguishing among humus forms (axis 1 and 2) and in understanding the factors involved in differentiating between exploited and preserved part of the forest.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies (Ponge 1993;Sadaka and Ponge 2003) and probably because of hierarchy, HMFA did not devote an axis to depth gradient. Nevertheless, careful examination of results shows that depth is a key criterion in distinguishing among humus forms (axis 1 and 2) and in understanding the factors involved in differentiating between exploited and preserved part of the forest.…”
Section: Discussioncontrasting
confidence: 99%
“…The different classes of litter/humus components were the active (main) variables, coded by their percentage of occurrence by volume. Passive variables (OL, OF, OH horizons, vegetation types, depth levels) were added in order to facilitate the interpretation of factorial axes (Sadaka and Ponge, 2003). All variables were transformed into X =(x − m) /s +20, where x is the original value, m is the mean of a given variable, and s is its standard deviation (Sadaka and Ponge, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Such relations have not been, however, extensively studied (Hirobe et al 2003;Karroum et al 2005;Carletti et al 2009;Trap et al 2011). Data are especially sparse for Mediterranean forest ecosystems (Sadaka and Ponge 2003;Tagger et al 2008), where both humus (Sevink et al 1989;van Wesemael and Verstraten 1993;Vacca 2000;Peltier et al 2001;Ponge 2003;Andreetta et al 2011) and microbial communities (e.g. Monokrousos et al 2004;Goberna et al 2005;Aponte et al 2010) have been found to be valuable indicators of responses of soil to the ecological constraints represented by long and variable summer droughts.…”
Section: Introductionmentioning
confidence: 95%